Vasoreactive Pulmonary Arterial Hypertension Manifesting With Misleading Epileptic Seizure: Diagnostic and Treatment Pitfalls - Farhat, Nesrine; Cools, Bjorn; Gewillig, Marc; Seghaye, Marie-Christine; Aggoun, Yacine; Beghetti, Maurice (Frontiers in Pediatrics, 2019)
A 5-year-old girl presented with acute nocturnal episodes of loss of consciousness following abdominal pain and cry. Epilepsy was primarily diagnosed but the course of the disease was suggestive of pulmonary hypertension. An adapted invasive assessment of pulmonary pressure and pharmacological challenge allowed for diagnosing vasoreactive pulmonary arterial hypertension. Initial treatment with sildenafil was not effective. Thus, calcium channel blockers were introduced when positive vasoreactivity was confirmed and permitted to stop the occurrence of the syncope and dramatically improved clinical status. At two years follow-up she is well without any complaint and in functional class I. Echocardiography shows slightly enlarged but not hypertrophied right ventricle with nearly normalized estimated right ventricular pressure. The last catheterization shows subnormal values of pulmonary arterial pressure (mean pulmonary artery pressure: 24 mmHg) and pulmonary vascular resistance (5, 4 Wood units*m²), normalizing with inhaled Nitric Oxide (mean pulmonary artery pressure of 14 mmHg and pulmonary vascular resistance of 1.5 Wood units*m²). Vasoreactive pulmonary arterial hypertension is a rare entity in children but it should not be misdiagnosed with seizures due to the presence of syncopal episodes. According to current knowledge, this form seems to have a better prognosis than non-reactive pulmonary arterial hypertension and the treatment of choice remains calcium channel blockers.